THE STRUCTURAL PROCESS AND THE INTERVENTION OF THE STF IN PUBLIC POLICIES RELATED TO THE BRAZILIAN PRISON SYSTEM FROM THE DECISION ON THE MERITS OF ADPF 347/DF - Rosa de Oliveira , Ciro (Revista Gênero e Interdisciplinaridade, 2025)
The article addresses the structural problem of the Brazilian prison system, highlighted by its continuous non-compliance with the principles of the Penal Execution Law (LEP). The Fundamental Precept Noncompliance Action (ADPF) 347, judged by the Brazilian Supreme Court (STF), revealed the gravity of this situation by recognizing the unconstitutional state of affairs (ECI) in the country’s prisons, emphasizing the need for judicial intervention to correct the State’s omissions and protect the fundamental rights of individuals deprived of liberty. The STF’s decision in ADPF 347 mandated a series of structural measures to reform the prison system, including expanding prison capacity, improving health and hygiene conditions, and strengthening rehabilitation and education programs within correctional facilities. These measures require coordinated actions between the Executive, Legislative, and Judiciary branches, highlighting the complexity of the issue and the necessity for robust interinstitutional cooperation. The National Council of Justice (CNJ), through the Department of Monitoring and Oversight of the Prison System and the Socioeducational Measures System (DMF), plays a crucial role in supervising and overseeing the prison system. Created by Law No. 12.106/2009, the DMF is responsible for monitoring prison conditions, conducting inspections, prison mutirões, and collecting data that guide the formulation of public policies aimed at improving prison conditions. The study concludes that only a coordinated and continuous effort between the State’s branches and the responsible institutions can transform the Brazilian prison system, overcoming the unconstitutional state of affairs and promoting a prison environment that respects and upholds fundamental rights.